The Psychosocial Experiences in Ex-Leprosy Patients: A Qualitative Study - Jufriyanto, Mohammad; Yusuf, Ah; Mundakir, Mundakir (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Ex-leprosy is a leprosy patient who has undergone treatment and is declared cured from a medical examination. The ex-leprosy have psychological and social problems due to disability and community stigma, caused them difficulty in re-socializing with the community. The aim is to identify the psychosocial experiences of ex leprosy in living their social life. This research is a phenomenological descriptive qualitative research method. The number of participants in this study were twelve using purposive sampling. Data collection using in-depth interviews and field notes, analyzed by the Collaizi method. This study produced six main themes, Social stigma, Support system, Able to do activities, Response to stress, Coping strategies, and Social support. Participants' social activity after recovering from leprosy has increased although there is still a stigma in some communities. Support from family and community is needed as well as good coping mechanisms for ex leprosy patients.